2010
DOI: 10.1097/aog.0b013e3181f0bc08
|View full text |Cite
|
Sign up to set email alerts
|

Single Umbilical Artery Risk Factors and Pregnancy Outcomes

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
112
1
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 34 publications
10
112
1
19
Order By: Relevance
“…[11][12][13][14][15] Neonates with isolated single umbilical artery have increased rates of growth restriction (10.9% compared with 25.0%) and estimated fetal weight less than the 10th percentile (odds ratio 2.23; 95% confidence interval [CI] 1.84-2.69). 16 In our institution, we recommend a fetal growth ultrasound examination at 32 weeks of gestation or pregnancies complicated with single umbilical artery. If the follow-up growth ultrasound scan is normal, with an estimated fetal weight more than the 10th percentile, we resume routine prenatal care.…”
Section: Ultrasound Findingsmentioning
confidence: 99%
“…[11][12][13][14][15] Neonates with isolated single umbilical artery have increased rates of growth restriction (10.9% compared with 25.0%) and estimated fetal weight less than the 10th percentile (odds ratio 2.23; 95% confidence interval [CI] 1.84-2.69). 16 In our institution, we recommend a fetal growth ultrasound examination at 32 weeks of gestation or pregnancies complicated with single umbilical artery. If the follow-up growth ultrasound scan is normal, with an estimated fetal weight more than the 10th percentile, we resume routine prenatal care.…”
Section: Ultrasound Findingsmentioning
confidence: 99%
“…Based on these findings, some authors have recommended that fetal growth should be monitored throughout pregnancy after prenatal diagnosis of a single umbilical artery. [7][8][9]11,12 As a matter of fact, throughout the study period, our management protocol for pregnancies diagnosed with ISUA included serial follow up fetal growth scans. And when fetal growth restriction was diagnosed additional fetal well being tests were performed.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11,[13][14][15]18,[20][21][22][23] On the other hand, all post-natal studies have shown that birth weight is significantly lower in ISUA pregnancies compared to control pregnancies. 5,9,10,12 This is possibly related to the fact that these are the studies with greater sample size. Moreover, since ISUA was not diagnosed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A two-vessel umbilical cord or single umbilical artery is seen in approximately 0.5%-1% of all deliveries, and it is the most common anomaly of the umbilical cord (1). Many risk factors have been suggested in previous studies, including maternal age, maternal smoking status, ethnicity, multiparity, and multiple gestations (2). Some studies have also indicated that risks of some adverse pregnancy outcomes such as intrauterine growth restriction, low birth weight, preterm delivery, and hypertensive disorders in pregnancy could be increased in cases with a single umbilical artery (3,4).…”
Section: Introductionmentioning
confidence: 99%